Reform of Hijab Heirs and Substitutes in the Islamic Inheritance Law System in Indonesia: Analysis of the Ta'lili Method of Reasoning for Grant Wills For Left Behind Heirs According to Syafi'iyah Fiqh - Muhammad Ikbal; Rusjdi Ali Muhammad; Muslim Zainuddin; Hafidh Ruhaimi (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2025)
The fundamental provisions of inheritance distribution in Islam refer to QS. An-Nisa’ verse 7, which guarantees inheritance rights for both men and women from the estates of parents and relatives. This is further clarified by a hadith narrated by Imam al-Bukhari regarding the position of grandchildren as substitutes for children in inheritance. However, there are differences in interpretation between Shafi'i jurisprudence (fiqh) and the Compilation of Islamic Law (KHI) regarding the implementation of these texts. This research employs a normative juridical method with a literature study and a descriptive-analytical approach to examine existing legal conceptions. The results indicate a classification of solutions for excluded (terhalang) heirs as follows: First Group: For grandchildren (orphans) of a son whose father predeceased the testator, the granting of a mandatory bequest (hibah wasiat) is obligatory. This is based on the nas (text) of the bequest verse, which remains applicable to them as close relatives who do not receive a direct share of the inheritance. Second and Third Groups: For siblings who are shielded (terhijab) and the dzawil arham group (other substitute heirs), the granting of a bequest is recommended (sunnah). In conclusion, reform through the instrument of hibah wasiat serves as a juridical solution to manifest justice for relatives who are normatively barred from receiving inheritance. This approach balances the legal certainty of the nas with social welfare for family members in need.